2019
DOI: 10.1002/jcp.29354
|View full text |Cite
|
Sign up to set email alerts
|

miR‐488 mediates negative regulation of the AKT/NF‐κB pathway by targeting Rac1 in LPS‐induced inflammation

Abstract: Endometritis is an inflammatory change in the structure of the endometrium due to various causes and is a common cause of infertility. Studies have confirmed that microRNAs (miRNAs) play a key regulatory role in various inflammatory diseases.However, the miRNA-mediated mechanism of endometrial inflammation induced by lipopolysaccharides (LPS) remains unclear. In this study, real-time quantitative polymerase chain reaction, Western blot analysis, immunofluorescence and Rac family small GTPase 1 (Rac1) interfere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…Previous studies have shown that miR-488 affects the pathophysiological processes of various diseases. [35][36][37] In this study, it was found that over-expression of miR-488-3p inhibited neuron apoptosis and alleviated cerebral infarction caused by ischemic stroke in mice, indicating that miR-488-3p might be a potential curative target for ischemic stroke. Previous studies have shown that VPS4 affects extracellular secretion and lysosomal and cell proliferation and differentiation through regulating specific signaling pathways.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Previous studies have shown that miR-488 affects the pathophysiological processes of various diseases. [35][36][37] In this study, it was found that over-expression of miR-488-3p inhibited neuron apoptosis and alleviated cerebral infarction caused by ischemic stroke in mice, indicating that miR-488-3p might be a potential curative target for ischemic stroke. Previous studies have shown that VPS4 affects extracellular secretion and lysosomal and cell proliferation and differentiation through regulating specific signaling pathways.…”
Section: Discussionmentioning
confidence: 70%
“…Some researchers have provided data showing that miR-488 expression is negatively regulated by inhibiting ROS and AKT/NF κB pathways in LPSinduced inflammation of intimal epithelial cells. 35 In osteosarcoma (OS) cells, miR-488 is down-regulated by targeting aquaporin 3 (AQP3) to inhibit cell proliferation and invasion, 37 indicating that miR-488 is a miRNA of tumor suppressor. Besides, miR-488 participates in drug tolerance of anti-cancer drug cisplatin mediated by eukaryotic translation initiation factor 3a (eIF3a) in non-small cell lung cancer cells (NSCLC).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that miRNAs play important roles in inflammation and cancer by regulating the NF-κB pathway ( 38 , 39 ). Nevertheless, whether miRNAs could be reversely regulated by NF-κB is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that miRNAs play important roles in in ammation and cancer by regulating the NF-κB pathway [33][34][35][36]. Nevertheless, whether miRNAs could be reversely regulated by NF-κB is largely unknown.…”
Section: Discussionmentioning
confidence: 99%